Excellent Front Desk Agent Service in Increasing Guest Satisfaction at Hotels in Bali - Venysia, Ni Putu Selina; Sekarti, Ni Ketut; Darmawijaya, I Gede (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This research aims to identify and group guest reviews of Front Desk Agent services at one of the hotels in Bali that provide a pleasant experience (Prima/WOW). Data was collected from guest reviews on OTA Tiket.com and Tripadvisor in the period January 2023 to May 2024. The results of the analysis showed four main themes that were prominent in guest reviews: The first theme, "Friendly and Polite," recorded the highest frequency with reviews emphasizing friendliness and professional attitude from the Front Desk Agent. The second theme, "Provides a Personal Touch," shows guests' appreciation for personal touches such as birthday wishes and room upgrades. The third theme, "Sprightly Provide Guest Needs," underscores the staff's proactive and quick response in meeting guest needs. The final theme, "Smooth Check-in Process," reflects the efficiency of the check-in process which is considered to make it very easy for guests. The results of this research indicate that Excellent/WOW service from the Front Desk Agent plays a significant role in increasing guest satisfaction at Hotel X.